2013
DOI: 10.1111/ijfs.12373
|View full text |Cite
|
Sign up to set email alerts
|

Co‐extrusion of pearl millet‐whey protein concentrate for expanded snacks

Abstract: Summary A study was conducted to develop pearl millet‐based extruded snacks with whey protein concentrate (WPC) to enhance its acceptability and nutritional value. Pearl millet grits (841 μ) was extruded with different levels (0%, 2.5%, 5.0% and 7.5%) of WPC at constant feed rate (10.5 kg h−1) and moisture content (14%). Addition of whey protein at 7.5% level significantly (P ≤ 0.05) increased Tg from 75.1 ± 0.26 °C to 120.5 ± 1.28 °C and Tm from 89.1 ± 1.51 °C to 158.7 ± 1.37 °C, which resulted in less expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 24 publications
5
48
0
Order By: Relevance
“…This might be due to lack of appropriate shear viscosity which unable to promote bubble growth and thereby making the product quite dense (Kristiawan et al, 2016). Similar results were noticed by Yadav et al, (2014) who reported that cell strength influenced by starch gelatinization and protein content. Hence, moisture content had significant effect on starch viscosity and physical attribute of extrudates (Gat and Ananthanarayan, 2015).…”
Section: Hardnesssupporting
confidence: 67%
See 3 more Smart Citations
“…This might be due to lack of appropriate shear viscosity which unable to promote bubble growth and thereby making the product quite dense (Kristiawan et al, 2016). Similar results were noticed by Yadav et al, (2014) who reported that cell strength influenced by starch gelatinization and protein content. Hence, moisture content had significant effect on starch viscosity and physical attribute of extrudates (Gat and Ananthanarayan, 2015).…”
Section: Hardnesssupporting
confidence: 67%
“…Pearl millet commonly known as bajra and termed as "nutricereal" due to presence of complex carbohydrates, protein of good biological activity, lipid, vitamins and minerals. It also contains high proportion of dietary fibers, and other phytochemicals with nutraceutical properties (Sihag et al, 2015 andYadav et al, 2014). However, it has remained as the food for poor and traditional consumers because of limited availability of ready-to-use or ready-to-eat pearl millet based products.…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 1607-1617mentioning
confidence: 99%
See 2 more Smart Citations
“…Whey is the serum or liquid part of milk that is a by-product of cheese and curd manufacturing (stobaugh et al, 2016). Incorporation of 5% Whey Protein Concentrate (WPC) in pearl millet grits (841 µ) was recommended to develop nutritious acceptable extruded snacks (Yadav et al, 2014). Nutritious high-protein puffed snacks of corn meal with texturized whey protein isolate was developed with acceptable physico-chemical properties.…”
Section: Milk Based Extruded Snacksmentioning
confidence: 99%